Fluoride and calcium release from peppermint-flavored fluoride varnish containing dicalcium-phosphate-dihydrate coated with xylitol - Yosi Kusuma Eriwati; Dhea Putriani; Karen Geraldine; Heri Hermansyah (Elsevier, 2022)
Bakground: Fluoride varnish with high initial fluoride and calcium release can help patients with high-risk caries. Ample quantities of free fluoride and calcium ions in the oral cavity can enhance enamel remineralization. This study aimed to investigate the effect of dicalcium phosphate dihydrate coated with xylitol (DCPD-xylitol), in fluoride varnish, on the release of fluoride and calcium ions in the oral cavity. Materials and methods: DCPD powder with xylitol was synthesized by preparing a 60% xylitol solution and mixed it with DCPD solution. The mixture was stirred for 1 h at room temperature and dried at 80 °C for 18 h to reduce the water content. Then, the powder was used in the formulation of peppermint-flavored fluoride varnish as an active agent. The amounts of fluoride and calcium ion released in deionized water at 37 °C for 6 h were assessed with an ion-selective electrode. The cumulative fluoride and calcium ion release data were analyzed using one-way analysis of variance (ANOVA) and the post hoc Tukey test with α = 0.05. Results: The results showed that the addition of DCPD coated with xylitol provided better bioavailability of the ions than DCPD without coating. Peppermint-flavored fluoride varnish (PFFV) with DCPD-xylitol 1% gave the highest fluoride ion release (296.90 mg/L) compared to the varnishes with other xylitol concentrations and the positive control. In contrast, PFFV DCPD-xylitol 5% afforded the highest calcium ion release at 111.20 mg/L. Conclusions: This study concluded that xylitol affects the bioavailability of free fluoride and calcium ions in varnishes. However, the efficacy of fluoride and calcium uptake in enamel and under different in vitro media conditions requires further investigation.